Nonvolant mammals of the Grota do Angico Natural Monument, northeast of Brazil: a complementary approach to the small species - Freitas, Evellyn B. de; De-Carvalho, Crizanto B.; Beltrão, Raone; Rocha, Stéphanie M.; Marques, Eduardo; Ruiz-Esparza, Juan; Rocha, Patrício A.; Ferrari, Stephen F. (Natureza Online, 2017)
The Brazilian Caatinga are the most den-sely populated semiarid zone of the planet. Despi-te this, the local biota and ecological processes are still poorly known. The biota of the Brazilian state of Sergipe is also poorly known, although half of which is part of the Caatinga, currently with about 10% of forest remnants. In order to better understand the mammal community of the Caatinga of Sergipe, in the present study, we inventoried the nonvolant mammalian fauna (mainly small species) of the se-miarid protected area Grota do Angico Natural Mo-nument (GANM; 2,138 ha), between January and December, 2010. We collected data through direct observation, records of vestiges (feces, tracks), reports from local residents, and trapping (pitfall, Sher-man, and Tomahawk traps) on five days each month, evaluating sampling efficiency and estimating spe-cies richness by using the cumulative species curve and the estimator Jackknife 1, respectively. We recor-ded 16 species, representing 11 families and 5 orders. Rodentia (n = 6) was the most representative order, followed by Carnivora (n = 5), and Didelphimorphia (n = 3), with only one species reported exclusively by local residents (Hydrochoerus hydrochaeris). The orders Cingulata and Primates had one species each. With seven captured species, the estimated species richness (Jack 1, 8.8±1.8) indicated no differences between capturing and potential richness. The reports of the occurrence of medium/large-bodied mammals in the recent past (e.g., Pecari, Dasypus, Sylvilagus, Galictis, and Dasyprocta) indicate a probable local extinction due to hunting pressure and/or habitat reduction/fragmentation. As a complementary appro-ach, the GANM currently has 20 mammal species, while the Caatinga of Sergipe counts a total of 31 mammal species. Despite the absence of large-bo-died species and some predators, the present results highlight the importance of the GANM in the con-servation of the local fauna and the ecosystems of the region, contributing to the understanding of the diversity of mammals in the Caatinga of Sergipe.